STUDI LITERATUR: MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI SMK - Arofah, Zulfi; Nafiati, Dewi Amaliah; Hendaryati, Neni; Apriani Fr, Dewi (Universitas Tanjungpura, 2025)
Education is a lifelong process aimed at developing individuals' potential across various aspects of life. One of the factors influencing educational success is students' learning interest, as it serves as an internal drive that motivates students to be more active and enthusiastic in participating in the learning process. Project Based Learning (PjBL) is considered one of the effective learning models for enhancing students' interest through active engagement in realworld projects. This article aims to examine the implementation of the Project Based Learning model in increasing students' learning interest at Vocational High Schools (SMK), particularly in the subject of Basic Accounting. The research method used is a literature study with a descriptive qualitative approach by reviewing various journals, articles, and other relevant sources. The findings indicate that PjBL is capable of creating an active, contextual, and meaningful learning environment while fostering the development of 21stcentury skills such as critical thinking, creativity, collaboration, and communication. The implementation of PJBL is seen as effective in linking learning to the demands of the professional world, thus strongly recommended to increase students' learning interest in SMK and prepare them for future career challenges.